KEKERASAN TERHADAP PEREMPUAN DALAM AL-QUR’AN - Zahra, Erfani (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2008)
Marital rape is the practice widely happened in various parts of countries. The main cause of the case is the perception, which regards the position of men, is higher than women. This is contrary to the principles of Islam. Islam regards all people are equal in humanity, and denounce all forms of violence and oppression, especially in a conjugal relation. Actually, from all forms of violence and oppression, al-Qurâ€™an clearly denounces not only marital rape, but also all kind of oppression and violence, especially those related to women. Therefore, all that lead toÂ the disadvantage of women is forbidden. Polygamy, divorce, revocation (ruju`) with negative motives, prostitution, raping, and all that humiliate holistic values are denounced by God.Keywords: Islam, marital rape.